Emotional intelligence subdimensions as moderators in the association between body dissatisfaction and symptoms of eating disorders among female Mexican adolescents. - Castro-López, Violeta R.; Franco-Paredes, Karina; Peláez-Fernández, María Ángeles; Trujillo Chi Vacuán, Eva María (Wiley, 2023)
Strong empirical research has shown a relationship between body dissatisfaction and symptoms of eating disorders (ED) and the direct and combined influenceof emotional factors and dimensions of emotional intelligence (EI) on ED symptoms. However, whether these emotional variables and competencies moderate the well-established relationship between body dissatisfaction and ED symptomatology has not yet been tested. Neither have studies of this nature been performed among high at-risk populations such as Mexican female adolescents. Thus, this research aimed to explore the moderator role of EI subdimensions in the relationship between body dissatisfaction and ED symptoms among female adolescents from Sinaloa, Mexico. A total of 485 female adolescents aged 14–19 years old (M=16.81,SD=1.33) who were students in middle school, high school, and college completed questionnaires about body dissatisfaction, ED symptomatology, and EI. We conducted moderating analyses. Subdimensions of EI significantly moderated the relationship between body dissatisfaction and symptoms of ED. For participants high in body dissatisfaction, lower levels in stress management ability and higher levels in the interpersonal EI and Adaptability EI dimensions were associated with higher levels of ED symptomatology. Subdimensions of EI have an important role in moderating the association between body dissatisfaction and symptoms of ED. The findings of this study contribute to improving the knowledge about the role of emotional competencies in ED. Proposals for future research and to improve preventative approaches are discussed.
Public Significance Statement:This study shows the moderating role of EI dimensions in the well-established relationship between body dissatisfaction and ED symptomatology. The research was conducted with a population at high risk of ED: female adolescents in the northwest of Mexico. Results showed that low Stress managementEI, high Adaptability EI, and high Interpersonal EI were associated with higher levels of ED symptomatology among participants with high (but not low) body dissatisfaction. These insightful results have theoretical and practical implications.
Keywords: Adolescentes - Trastornos nutricionales; Emociones; Inteligencia; Adolescentes - Psicología; Adolescents; Body dissatisfaction; Eating disorder symptoms; Emotional intelligence; Moderation